Reviving the Children of Nimrod - Pinn, A. author. aut Link
XXIII, 144 p.
Keywords: As Anthony Pinn argues in his latest collection, humanism comes in many colors. When more attention is given to issues of race as connected to other forms of oppression, it is easier to see the manner in which humanism has lived and functioned within African American communities. Using the biblical figure Nimrod as symbol, African American Humanist Principles demonstrates African American humanists' intellectual and praxis-related grounding in a history of rebellion against over-determined and oppressive limitations on human doing and being. Pinn maintains that it is this quest for a fuller sense of being - for greater existential and ontological worth - that informs the basic principles of African American humanism. African American Humanist Principles is one of the only books to present the inner workings of humanist principles as the foundation for humanism from the African American perspective - its form and content, nature and meaning.